Meta-analysis of the prevalence of malaria associated with pregnancy in Colombia 2000-2020. - Jaiberth Antonio Cardona-Arias; Jaime Carmona-Fonseca (PLoS ONE, 2021)
Knowledge about malaria associated with pregnancy is scarce in Latin America, and in Colombia, little is known about the magnitude of this infection. A systematic review was conducted to determine the prevalence of malaria associated with pregnancy (MAP) and each of its three forms: gestational (GM), placental (PM), and congenital (CM) tested using thick blood smear (TBS) and PCR. Also to compare the proportion of cases due to Plasmodium falciparum and Plasmodium vivax in Colombia from the year 2000-2020. We searched in Pubmed, Science Direct, EMBASE, EMCare, Cochrane Library, Scielo, Lilacs, Google Scholar, libraries, and repositories of Colombian universities, to obtain data on prevalence of GM, PM and CM with their respective testing method. We performed a meta-analysis with a random-effects model to obtain pooled prevalence of MAP and its three forms categorized by testing methods (TBS and PCR). We used data from 14 studies (out of 258 screened) contributing 7932, 2506 women for GM and PM respectively, also data on 1143 umbilical cord blood samples, and 899 peripheral blood of neonates. We found prevalence by TBS as, MAP 4.5% (95%CI = 2.9-6.9), GM 5.8% (95%CI = 3.8-8.7), PM 3.4% (95%CI = 1.7-6.7) and CM 1.3% (95%CI = 0.6-3.0). With PCR the prevalence was, MAP 14.4% (95%CI = 7.6-25.5), GM 16.7% (95%CI = 9.0-28.8), PM 11.0% (95%CI = 4.1-26.3) and CM 16.2% (95%CI = 8.2-29.5). The prevalence of submicroscopic infection was 8.5% (95%CI = 3.4-19.7) in GM, 10.1% (95%CI = 3.5-25.5) in PM and 22.0% (95%CI = 13.2-34.3) in CM. Infections by P. vivax was dominant over P. falciparum when tested with TBS, the PCR test gave similar proportions of P. falciparum and P. vivax. This meta-analysis has demonstrated high prevalence of MAP in Colombia, and highlights the urgent need to increase attention of researchers, research funding institutions, government agencies, and health authorities to study and intervene MAP, that has currently been under investigated.